2017
DOI: 10.21037/jss.2017.08.16
|View full text |Cite
|
Sign up to set email alerts
|

Does the law of diminishing returns apply to the lengthening of the MCGR rod in early onset scoliosis with reference to growth velocity?

Abstract: The 'law of diminishing returns' does not affect serial lengthening of MCGR in the way that has been observed using TGR. It was also demonstrated that in the MCGR group growth velocity was maintained relative to that of the normal spine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 14 publications
1
15
0
Order By: Relevance
“…Such measurements have been reported to be very accurate. 17 , 25 As seen from our results, instrumentation length gains were consistent with height gains throughout treatment while T1-T12 and T1-S1 spinal length did not reflect growth as consistently. Coronal spinal length measurements are thus inherently unreliable and alternatives such as sagittal spine length measurements may be preferable.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Such measurements have been reported to be very accurate. 17 , 25 As seen from our results, instrumentation length gains were consistent with height gains throughout treatment while T1-T12 and T1-S1 spinal length did not reflect growth as consistently. Coronal spinal length measurements are thus inherently unreliable and alternatives such as sagittal spine length measurements may be preferable.…”
Section: Discussionsupporting
confidence: 73%
“…30 Thus, "law of temporary diminishing distraction gains" may be a more appropriate term to use for describing such reductions in MCGR lengthening observed here and in past studies. 11,12,24,25 The interesting feature of the "law of temporary diminishing distraction gains" is that it is a phenomenon unique only to the currently implanted rod under distraction. The gradual reductions of rod lengthening illustrated by increasing divergence between targeted and achieved length gains is only temporary.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ahmad et al 15 reported on a reduced lengthening potential after an average of 30 months and Studer et al 16 after an average of 25 months. On the contrary, Cheung et al 22 , 23 as well as Gardner 24 found no ‘law of diminishing returns’ after 46, 50 and 24 months follow-up respectively.…”
Section: Discussionmentioning
confidence: 96%
“…21 The short-term results with MCGRs contradict in terms of diminishing returns and may be related to the large variations in distraction techniques and frequencies. 23,49,59,60 Ahmad et al 59 suggested in the short-term follow-up that this rate of decline is gradual as compared to the rapid decline seen in TGR. There is apparent divergence observed between targeted (intended amount of lengthened input in the external remote controller) and achieved (actual length measured on radiographs or ultrasound) lengthening with increasing MCGR distraction.…”
Section: Complicationsmentioning
confidence: 99%